2009
DOI: 10.1016/j.pneurobio.2009.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Assessing neuronal networks: Understanding Alzheimer's disease

Abstract: Findings derived from neuroimaging of the structural and functional organization of the human brain have led to the widely supported hypothesis that neuronal networks of temporally coordinated brain activity across different regional brain structures underpin cognitive function. Failure of integration within a network leads to cognitive dysfunction. The current discussion on Alzheimer's disease (AD) argues that it presents in part a disconnection syndrome. Studies using functional magnetic resonance imaging, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
78
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(87 citation statements)
references
References 113 publications
(125 reference statements)
8
78
0
1
Order By: Relevance
“…These deficits are commonly associated with abnormal brain rhythms, including disturbances in Îł frequency (30-80 Hz) oscillations (GFO) in corticocortical and thalamocortical (TC) circuits (Bokde et al, 2009;Clinton and Meador-Woodruff, 2004;de Haan W. et al, 2009;Friston, 2002;Herrmann and Demiralp, 2005;Light et al, 2006;Lisman, 2011;Meyer-Lindenberg, 2010;Pinault, 2011;Spencer et al, 2003;Uhlhaas and Singer, 2006). At least four types of GFO should be considered: 1) Spontaneously-occurring (baseline) GFO, which are dominant during desynchronized state of the electroencephalogram (Jasper, 1936;Sheer, 1975); 2) Sensory-evoked GFO, which are phase-locked to the stimulus onset (Pantev et al, 1991;Spencer et al, 2008b); 3) Steadystate GFO during repetitive sensory stimulation (Regan and Spekreijse, 1986); and 4) Cognition or perception-related induced synchronized GFO (Gray et al, 1989;Joliot et al, 1994;Sheer, 1975).…”
mentioning
confidence: 99%
“…These deficits are commonly associated with abnormal brain rhythms, including disturbances in Îł frequency (30-80 Hz) oscillations (GFO) in corticocortical and thalamocortical (TC) circuits (Bokde et al, 2009;Clinton and Meador-Woodruff, 2004;de Haan W. et al, 2009;Friston, 2002;Herrmann and Demiralp, 2005;Light et al, 2006;Lisman, 2011;Meyer-Lindenberg, 2010;Pinault, 2011;Spencer et al, 2003;Uhlhaas and Singer, 2006). At least four types of GFO should be considered: 1) Spontaneously-occurring (baseline) GFO, which are dominant during desynchronized state of the electroencephalogram (Jasper, 1936;Sheer, 1975); 2) Sensory-evoked GFO, which are phase-locked to the stimulus onset (Pantev et al, 1991;Spencer et al, 2008b); 3) Steadystate GFO during repetitive sensory stimulation (Regan and Spekreijse, 1986); and 4) Cognition or perception-related induced synchronized GFO (Gray et al, 1989;Joliot et al, 1994;Sheer, 1975).…”
mentioning
confidence: 99%
“…It can also be mathematically described as the temporal coherence or statistical dependence of activity between different nerve cells or their circuits. 30 Functional disconnections have been hypothesized in mild cognitive impairment, 31 schizophrenia, 32 Parkinson disease, 33 multiple sclerosis, 34 neglect, 35 autism, 36 Alzheimer disease, 37 behavioral changes, 38 alexia, 39 and more. The common trait between these conditions is the altered function of the nervous system that creates a functional loss of capacity in a patient's health or behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Using DTI and fMRI, Teipel et al [100] and Greicius et al [101] showed that functional connectivity across the entire DMN is based on a distinct pattern of anatomical connectivity within the cerebral white matter. In addition, some psychiatric diseases, such as schizophrenia [102] , AD [103][104][105] , and epilepsy [106] , also demonstrate a decreased WMM connectivity within the DMN. In a recent review [4] , Hulvershorn et al used a dMRI-derived network to systematically review the dysfunctional connectivity in pediatric MDD.…”
Section: Dmri Network-based Applications In Neuropsychiatric Diseasementioning
confidence: 99%